Capital Flow Management Measures in the Digital Age : Challenges of Crypto Assets - He, Dong (FinTech Notes; FinTech Notes ;, 2022)
Capital flow management measures (CFMs) can be part of the broader policy toolkit to help countries reap the benefits of capital flows while managing the associated risks. Their implementation typically requires that financial intermediaries verify the nature of transactions and the identities of transacting parties but is facing the rising challenge of crypto assets. Indeed, crypto assets have become a significant instrument for payments and speculative investments in some countries. They can be traded pseudonymously and held without identification of the residency of the asset holder. Many crypto service providers operate across borders, making supervision and enforcement by national authorities more difficult. The challenges posed by the attributes of crypto assets are compounded by gaps in the legal and regulatory frameworks. This paper aims to discuss how crypto assets could impact the effectiveness of CFMs from a structural and longer-term perspective. To preserve the effectiveness of CFMs against crypto-related challenges, policymakers need to consider a multifaceted strategy whose essential elements include clarifying the legal status of crypto assets and ensuring that CFM laws and regulations cover them; devising a comprehensive, consistent, and coordinated regulatory approach to crypto assets and applying it effectively to CFMs; establishing international collaborative arrangements for supervision of crypto assets; addressing data gaps and leveraging technology (regtech and suptech) to create anomaly-detection models and red-flag indicators that will allow for timely risk monitoring and CFM implementation.